2021
DOI: 10.1097/adm.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Legalization and Adolescent Use of Electronic Vapor Products, Cannabis, and Cigarettes

Abstract: Objectives: Cannabis legalization may have unintended consequences, such as effects on prevalence of adolescent use of other substances. We hypothesize that in states that have legalized recreational cannabis (RCL states), electronic vapor product use (''vaping''), cannabis, and cigarette use among adolescents is more prevalent than in states that have only legalized medical cannabis (MCL states) and states that have neither legalized recreational nor medical cannabis (NL states). Methods: Data are from the Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Cannabis, a drug derived from the Cannabis plant, is the most widely used illicit psychoactive substance worldwide, with a steady increase in usage over the past decade in the setting of increased legalization of recreational marijuana use 1 , 2 . Cannabis use has been associated with various psychiatric comorbidities 3 , including substance use disorders and schizophrenia 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis, a drug derived from the Cannabis plant, is the most widely used illicit psychoactive substance worldwide, with a steady increase in usage over the past decade in the setting of increased legalization of recreational marijuana use 1 , 2 . Cannabis use has been associated with various psychiatric comorbidities 3 , including substance use disorders and schizophrenia 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Indeed, adolescent cannabis vaping prevalence is higher in some states with legalized cannabis for adults. 37 Marketing efforts for a wide variety of cannabis products have proliferated in the legalized cannabis environment; these campaigns are viewed frequently by adolescents, 38,39 and probably influence their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, cannabis products are generally more available to youth as more states allow legalized use for adults, although the impact of these laws on youth cannabis use remains inconsistent and generally null 31–36 . Indeed, adolescent cannabis vaping prevalence is higher in some states with legalized cannabis for adults 37 . Marketing efforts for a wide variety of cannabis products have proliferated in the legalized cannabis environment; these campaigns are viewed frequently by adolescents, 38,39 and probably influence their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A study using the Consumer Expenditure Interview Survey found that households in RCL states increased their spending on food and alcohol, indicating a connection between cannabis, food and alcohol use [38]. Three studies using the US Behavioral Risk Factor Surveillance System and YRBS data found a significant association between RCL with increased alcohol use, primarily among younger adults and men [39], electronic vapor product use (''vaping''), cannabis, and cigarette use [40] and a small increase in the likelihood of any e-cigarette use among adolescents [41]. Similarly, data from the first four waves (2013-2018) of the PATH study shows a significant association between baseline past-30-day e-cigarette use and past-30-day cannabis use at 12-month follow-up (AOR¼5.92, CI: 3.52, 9.95) among adolescents who have never used cannabis at baseline, with AOR being higher among adolescents living in RCL states (AOR¼18.39; CI: 4.25, 79.68) than that of adolescents in NL states (AOR¼5.09; CI: 2.86, 9.07), indicating the effect modification of state RCL law on this association [42].…”
Section: Other Substance Usementioning
confidence: 99%